Compound Composite Odontoma and Its Management - Morawala Abdul; Kapila Pragati; Chunawala Yusuf (Hindawi Limited, 2014)
Odontomas are odontogenic benign tumors composed of dental tissue. Majority of these lesions are asymptomatic and are often detected on routine radiographs. They can be thought of as "tooth hamartomas" with the lesion consisting of various tooth components. They are divided histologically into complex odontomas and compound odontomas. This paper describes the case of a compound odontoma in a 13-year-old girl diagnosed due to the retention of the primary right mandibular second molar. A surgical excision was performed without disturbing the unerupted premolar. The results achieved indicate that early diagnosis of odontomas enables adoption of less complex treatment, a better prognosis, and displacement or devitalisation of adjacent tooth.